Stored energy control for long-term continuous operation of an electric and hydrogen hybrid energy storage system for emergency power supply and solar power fluctuation compensation. (29th March 2019) - Zhang, Z.; Nagasaki, Y.; Miyagi, D.; Tsuda, M.; Komagome, T.; Tsukada, K.; Hamajima, T.; Ayakawa, H.; Ishii, Y.; Yonekura, D.
Abstract: In order to realize a large-capacity stand-alone emergency power supply that enables highly reliable and high-quality power supply at the time of a large-scale natural disaster and enables effective use of solar power generation, we proposed an electric and hydrogen hybrid energy storage system (HESS). It is composed of an electric double-layer capacitor bank, fuel cell, electrolyzer, and hydrogen storage (buffer gas tank and metal hydride). In an emergency, this HESS is expected to supply power for loads together with photovoltaics panels for a long time. In usual time, it should not only cooperate with external electricity grids to convert unstable photovoltaic output power into reliable power supply, but also maintain sufficient stored energy in case of emergency. To realize the continuous operation of the HESS in both emergency and usual time, we proposed an electric double-layer capacitor's state-of-charge feedback control method and a hydrogen energy feedback control method, coordinating an energy management method based on Kalman filter algorithm. An experiment and a simulation demonstrated the operations of a 10-kW scale model HESS in emergency and usual time mode, respectively. The demonstrations verified the correct performance of the proposed HESS with the proposed control methods and enabled the continuous operation of the HESS. Highlights: Developed energy control methods in an electric and hydrogen energy storage system. Enabled long-time continuous operation of the system by the energy control methods. Verified system's operation as stand-alone emergency power supply by an experiment. Verified the operation for effective on-grid PV power generation by a simulation.